CRISPR/Cas9-mediated targeted mutagenesis of GmTCP19L increasing susceptibility to Phytophthora sojae in soybean. - Sujie Fan; Zhuo Zhang; Yang Song; Jun Zhang; Piwu Wang (PLoS ONE, 2022)
The TEOSINTE BRANCHED1/CYCLOIDEA/PROLIFERATING CELL FACTOR (TCP) transcription factors is one of the superfamilies of plant-specific transcription factors involved in plant growth, development, and biotic and abiotic stress. However, there is no report on the research of the TCP transcription factors in soybean response to Phytophthora sojae. In this study, Agrobacterium-mediated transformation was used to introduce the CRISPR/Cas9 expression vector into soybean cultivar "Williams 82" and generated targeted mutants of GmTCP19L gene, which was previously related to involve in soybean responses to P. sojae. We obtained the tcp19l mutants with 2-bp deletion at GmTCP19L coding region, and the frameshift mutations produced premature translation termination codons and truncated GmTCP19L proteins, increasing susceptibility to P. sojae in the T2-generation. These results suggest that GmTCP19L encodes a TCP transcription factor that affects plant defense in soybean. The new soybean germplasm with homozygous tcp19l mutations but the BAR and Cas9 sequences were undetectable using strip and PCR methods, respectively, suggesting directions for the breeding or genetic engineering of disease-resistant soybean plants.